2012
DOI: 10.1021/ma202764v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photophysical and Photovoltaic Properties of Conjugated Polymers Containing Fused Donor–Acceptor Dithienopyrrolobenzothiadiazole and Dithienopyrroloquinoxaline Arenes

Abstract: We have developed two nitrogen-bridged pentacyclic donor–acceptor dithienopyrrolobenzothiadiazole (DTPBT) and dithienopyrroloquinoxaline (DTPQX) arenes where the two outer electron-rich thiophene moieties are covalently fastened with the central electron-deficient benzothiadiazole and quinoxaline cores by two nitrogen bridges. These rigid and coplanar DTPBT and DTPQX building blocks were copolymerized with fluorene (F), carbazole (C) and cyclopentadithiophene (CPDT) units via Suzuki or Stille coupling polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 45 publications
0
50
0
Order By: Relevance
“…These polymers exhibited blue-shifted absorption spectra relative to DTBT-based and DTPBT-based polymers. In detail, the absorption edge of P2 is 502 nm in film, however, the polymer PCDTBT [35] is 660 nm and PCDTPBT [32] is 570 nm. The results were quite opposite to what we had expected.…”
Section: Synthesis and Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…These polymers exhibited blue-shifted absorption spectra relative to DTBT-based and DTPBT-based polymers. In detail, the absorption edge of P2 is 502 nm in film, however, the polymer PCDTBT [35] is 660 nm and PCDTPBT [32] is 570 nm. The results were quite opposite to what we had expected.…”
Section: Synthesis and Characterizationmentioning
confidence: 95%
“…Therefore, fused-ring building blocks are widely used in synthesis of conjugated polymers, such as naphtho [2,3-b:6,7-d 0 ]dithiophene (NDT) [27], thienyl-phenylene-thienylene-phenylene-thienyl (TPTPT) [28], indaceno dithiophene (IDTT) [29], naphtho-[1,2-c:5,6-c]bis [1,2,5]-thiadiazole (NT) [30,31]. Cheng et al reported a multifused DTPBT unit (Scheme 1) [32], which was prepared by covalently fastening adjacent electron-rich donor (thieno [3,2-b]pyrrole) and electron-deficient acceptor (BT). The monomer was used to construct D-A polymers by copolymerizing with different donor units.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Compared to small molecules, the conjugated oligomers, especially those with ribbon-or ladder-type frameworks, not only form graphene-like structures, but also possess some unique characteristics such as largely defect-free accurate structures and excellent film forming properties. [29][30][31][32] Compared with physical methods, chemical synthesis could precisely control the structure to give the desired shape and dimension of the achieved products. [26][27][28] Up to now there exist two principal chemical methods to synthesize ladder-type materials: one is the polymerization of some multifunctional monomers, generating a ladder type material in just a single reaction; the other is the cyclization of suitably functionalized open-chain precursors in a polymerhomologous process.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn leads to a reduced optical bandgap and a red-shifted absorption spectrum [31][32][33][34]. In doi: 10.1007/s11426-014-5221-9 addition, molecules with coplanar and rigid structure usually have smaller reorganization energy, which is beneficial for achieving high charge-carrier mobility [35][36][37][38][39]. Recently, we reported two novel polyaromatics based on carbazole: dithieno [2,3-b;7, 6-b] carbazole (C1) and dithieno[3,2-b; 6,7-b]carbazole (C2).…”
Section: Introductionmentioning
confidence: 99%